Collagen dehydration - Haverkamp RG; Sizeland KH; Wells HC; Kamma-Lorger C (Elsevier BV)
Type I collagen is a ubiquitous structural protein in animal tissues. It is normally present in a hydrated form. However, collagen is very dependent on associated water for its mechanical properties. In skin, where type I collagen is dominant, there is a longstanding concern that the skin and therefore collagen may partially dry out and result in structural degradation. Here we show that dehydration of type I collagen fibrils, using 2-propanol, results in a two-stage dehydration process. Initially, the fibrils do not change length, i.e. the D-period remains constant, but shrinkage occurs within the fibrils by an increase in the gap region and a decrease in the overlap region within a D-band and a shortening of the helical turn distance and fibril diameter. Only with further dehydration does the length of the collagen fibril decrease (a decrease in D-period). This mechanism explains why collagen materials are resistant to gross structural change in the early stages of dehydration and shows why they may then suffer from sudden external shrinkage with further dehydration.
Keywords: Collagen; Dehydration; Small angle X-ray scattering; Animals; Collagen; Collagen Type I; Dehydration; Extracellular Matrix; Skin; 0601 Biochemistry and Cell Biology